Thermogenic Effect of Glucose in Hypothyroid Subjects. (10th March 2014) - Kozacz, Agnieszka; Grunt, Paulina; Steczkowska, Marta; Mikulski, Tomasz; Dąbrowski, Jan; Górecka, Monika; Sanocka, Urszula; Ziemba, Andrzej Wojciech
Abstract : The importance of thyroid hormone, catecholamines, and insulin in modification of the thermogenic effect of glucose (TEG) was examined in 34 healthy and 32 hypothyroid subjects. We calculated the energy expenditure at rest and during oral glucose tolerance test. Blood samples for determinations of glucose, plasma insulin, adrenaline (A), and noradrenaline (NA) were collected. It was found that TEG was lower in hypothyroid than in control group (19.68 ± 3.90 versus 55.40 ± 7.32  kJ, resp., P < 0.0004 ). Mean values of glucose and insulin areas under the curve were higher in women with hypothyroidism than in control group (286.79 ± 23.65 versus 188.41 ± 15.84  mmol/L·min, P < 0.003 and 7563.27 ± 863.65 versus 4987.72 ± 583.88  mU/L·min, P < 0.03 resp.). Maximal levels of catecholamines after glucose ingestion were higher in hypothyroid patients than in control subjects (Amax—0.69 ± 0.08 versus 0.30 ± 0.07  nmol/L, P < 0.0001, and NAmax—6.42 ± 0.86 versus 2.54 ± 0.30  nmol/L, P < 0.0002 ). It can be concluded that in hypothyroidism TEG and glucose tolerance are decreased while the adrenergic response to glucose administration is enhanced. Presumably, these changes are related to decreased insulin sensitivity and responsiveness to catecholamine action.